Finite Element Analysis Verification of Experimental Work Results of a Single Point Incremental Sheet Metal Forming of Aluminum 6061 - Noha Fouad; Ahmed El-Kaseer; Hassan Abd El-Hafez; Ahmed Nassef (Port Said Engineering Research Journal, 2017)
In this paper, finite-element modeling (FEM) was developed to simulate the incremental sheet metal forming technique. The study mainly focused on the manufacture of complex shapes and modeled using ABAQUS/Explicit finite-element code as a simulation tool. Accordingly, a series of simulation trials have been carried out and the obtained results validated via experimental tests. The results indicated that the increasing of incremental depth increased the deformation force and this causing an increase of the stress. Also, the increase of the incremental depth from 0.5 mm to 1.0 mm increasing the sheet thinning from 0.8 mm to 0.698 mm. Moreover, the increasing of feed rate increased the thinning with the same value for both of FEM and experimental tests. Furthermore, the results showed that the incremental depth has a significant effect on the surface roughness and sheet thickness and that feed rate have found to be the second effective parameter.